The role of multidisciplinary care in managing sarcoma in low- and middle-income countries: a focus on treatment outcomes - Mobolaji, Adebayo Adebayo; Badejo, Adebolu; Adegbesan, Abiodun; Akingbola, Adewunmi; Tundealao, Samuel; Morhason-Bello, Jemiludeen O.; Ajibola, Oladiran B.; Chuku, Joel (International Journal of Research in Orthopaedics, 2025)
Sarcomas are a heterogeneous group of rare malignancies requiring complex and individualized management strategies. In high-income settings, multidisciplinary care (MDC) has been shown to improve diagnostic accuracy, optimize treatment planning, and enhance patient outcomes. However, the role and implementation of MDC in managing sarcoma within low- and middle-income countries (LMICs) remain underexplored. This paper critically examines the impact of multidisciplinary care models on treatment outcomes for sarcoma patients in LMICs, highlighting current practices, barriers, and opportunities for improvement. Drawing on data from peer-reviewed literature, institutional reports, and global cancer care guidelines, we analyze how team-based approaches involving surgical oncologists, radiation oncologists, medical oncologists, radiologists, pathologists, and supportive care specialists influence early diagnosis, resection margins, recurrence rates, and survival outcomes. Findings indicate that while MDC improves adherence to evidence-based guidelines and fosters coordinated care, its effectiveness in LMICs is limited by workforce shortages, infrastructural deficits, and fragmented health systems. Nevertheless, innovative approaches such as virtual tumor boards, regional centers of excellence, and task-shifting models show promise in bridging gaps. Case studies from selected LMICs demonstrate that even in resource-constrained settings, structured multidisciplinary interventions can lead to earlier diagnosis, improved surgical planning, reduced treatment delays, and better quality of life (QoL). We conclude that scaling up MDC for sarcoma care in LMICs requires sustained investment in health system strengthening, interprofessional training, and policy support. Emphasizing locally adaptable MDC frameworks could significantly enhance sarcoma outcomes and contribute to closing the global cancer care gap.